Effects of hydroxyapatite filler on long-term hydrolytic degradation of PLLA/PCL porous scaffolds. (September 2015) - Rodenas-Rochina, Joaquin; Vidaurre, Ana; Castilla Cortázar, Isabel; Lebourg, Myriam
Abstract: Poly(L-lactic acid)(PLLA)/poly(ε-caprolactone)(PCL)/hydroxyapatite(HAp) composites appear as promising materials for healing large bone defects. Highly porous PLLA/PCL scaffolds, 80/20, 20/80 weight ratios, porosity >85%, were prepared by a dual technique of freeze extraction and porogen leaching, with and without HAp. A double pore structure was obtained, with interconnected macroporosity together with interconnected microporosity. Subsequent long-term (78 weeks = 1.5 years) hydrolytic degradation behavior was investigated in terms of the samples' mechanical properties, molecular weight (Mw ), mass changes, thermal characteristics, X-ray Diffraction and Thermogravimetric Analysis. Elastic modulus and yield strength of as-synthesized scaffolds were higher for PLLA rich blends and including the inorganic phase does not lead to a mechanical strengthening in these materials. Nevertheless, after 30 weeks of degradation, PLLA rich scaffolds lost more than half of their strength and rigidity. On the contrary, the densification modulus of the PLLA based blends increased with degradation time, whereas PCL-based blends had a relatively constant densification modulus. PCL-based samples showed lower hydrolysis coefficients k than PLLA-based samples, as expected from the higher density of ester bonds in the latter. Interestingly, although including HAp leads to a lower hydrolysis coefficient k in PCL rich samples, it increases k in the PLLA-based sample, which is consistent with the other results obtained.